2022
DOI: 10.1093/rheumatology/keac030
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and immune-related protein patterns of anti-MDA5 positive clinically amyopathic dermatomyositis Dutch patients

Abstract: Objectives The presence of melanoma differentiation-associated protein 5 (MDA5) antibodies in patients with dermatomyositis (DM) is associated with the development of a rapidly progressive interstitial lung disease (RPILD), unresponsive to conventional treatment. We characterize patients and provide more insight into potential biomarkers to identify patients with RPILD. Methods Patients diagnosed with anti-MDA5 positive DM be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Several studies found that a majority of MDA5 + DM or CADM patients presented elevated levels of serum cytokines, including IFN-a, IFN-b, IFN-g, IL-1b, IL-6, IL-10, IL-18 and IL-12 (62-64). Hensgens et al (65) found that signaling pathways of IFN, IL-1, IL-10 and IL-18 families upregulated in MDA5 + DM in comparison to healthy individuals. Increased C-C motif chemokine ligand 2 (CCL2), C-X-C motif chemokine ligand 9 (CXCL9) and CXCL10 could be also observed in CADM patients (64).…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found that a majority of MDA5 + DM or CADM patients presented elevated levels of serum cytokines, including IFN-a, IFN-b, IFN-g, IL-1b, IL-6, IL-10, IL-18 and IL-12 (62-64). Hensgens et al (65) found that signaling pathways of IFN, IL-1, IL-10 and IL-18 families upregulated in MDA5 + DM in comparison to healthy individuals. Increased C-C motif chemokine ligand 2 (CCL2), C-X-C motif chemokine ligand 9 (CXCL9) and CXCL10 could be also observed in CADM patients (64).…”
Section: Pathogenesismentioning
confidence: 99%
“…Hensgens et al. ( 65 ) found that signaling pathways of IFN, IL-1, IL-10 and IL-18 families upregulated in MDA5 + DM in comparison to healthy individuals. Increased C-C motif chemokine ligand 2 (CCL2), C-X-C motif chemokine ligand 9 (CXCL9) and CXCL10 could be also observed in CADM patients ( 64 ).…”
Section: Mas and Mda5 + Dmmentioning
confidence: 99%
“…In a recent single-centre retrospective Chinese cohort [35], three clusters emerged of which two were comparable to the French study: one mainly showing arthritis and mechanic's hands with low rates of RP-ILD and a good prognosis; one enriched in RP-ILD which was also exhibiting fever, hyperferritinemia and a far worse prognosis. In contrast, a different third cluster identified patients with high rates of typical cutaneous signs and enriched in clinically relevant myositis, with very low rates of RP-ILD (Table 1) [65].…”
Section: The Bedside: Clinical Clustersmentioning
confidence: 99%
“…One of the most common lung lesions in DM/PM patients is interstitial lung disease (ILD). Patients with this complication have high morbidity and mortality rates, ranging from 20% to 78% 12 . Salivary sugar chain antigen‐6 (KL‐6), as an indicator that can reflect lung injury, has been paid more and more attention by researchers 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with this complication have high morbidity and mortality rates, ranging from 20% to 78%. 12 Salivary sugar chain antigen‐6 (KL‐6), as an indicator that can reflect lung injury, has been paid more and more attention by researchers. 13 Importantly, DM patients with anti‐MDA5 antibodies face a significant risk of ILD and exhibit a quickly worsening disease trajectory, making early detection of this condition critical.…”
Section: Introductionmentioning
confidence: 99%